Patterns of surface water dynamics and storage changes in a basin of Bundelkhand Region, India: implications for water management - Bhatpuria, Dhyey; Sharma, Nitin; Amarnath, Giriraj; Sikka, Alok (Wiley, 2024)
Surface water is essential for agricultural, domestic and industrial production worldwide. Monitoring surface dynamics is crucial for sustainable ecosystems and global water resources. Importance of monitoring surface water dynamics is even more pronounced in the semi-arid regions worldwide. An analysis of surface water extent and volume change patterns has been conducted, comparing these dynamics with alterations in precipitation patterns within a basin in Central Bundelkhand, a semi-arid region in the Central India prone to droughts. To map the waterbodies, we leveraged Sentinel-1 SAR data using an automated mapping framework and utilised DEM dataset to extract bathymetry using interpolation with modifications using water persistence. Analysis revealed a lag in surface water peak water level with respect to accumulated rainfall by 2–3 months. Furthermore, we have categorised the water bodies into small, medium and large by surface area and found that smaller water bodies show a higher intra-annual variance, while medium and large water bodies show a lower intra-annual variance. The findings suggest that smaller communities reliant on smaller water bodies are at a higher risk from climate variability in the region and a delay in attaining peak surface storage across the basin causes further challenges to water management.